Estudo das propriedades geotécnicas do solo com aplicação na análise da estabilidade de talude da CE-356 - Costa, Ayrle Freitas da (2021)
Safety in engineering works is always a concern, mainly due to the numerous variables involved and the complexity of the works. In the Geotechnical area, projects demand even more attention and care, such as the analysis of slope stability, for example. Thus, this issue becomes a topic of great importance given the need for urban expansion and, consequently, occupation of unknown places. However, the analysis of slope stability is also not a common practice in the operation of highways. Due to the high flow of vehicles, any rupture that occurs on road slopes requires the recovery of these areas, which is often quite costly, as well as having large-scale consequences, both environmental and loss of life. In many cases, these ruptures could be avoided or minimized, if there were a previous and continuous study on the stability of these road slopes. Therefore, this work aims to characterize the existing soil on the slope of CE-356, a stretch that connects Russas/CE to Baraúna/RN. After this characterization, the slope stability was analyzed in the SLOPE/W software, to obtain the safety factor, performing five simulations, one for each analysis method (Fellenius, Bishop, Janbu, Spencer and Morgenstern-Price) in order to compare The obtained results. It was verified that the FS in all methods was below 1.5, noting an instability on the slope and the possibility of rupture.